Prevalence and clustering of modifiable risk factors of cardiovascular disease in rural residents of Luoping county, Yunnan province: a com-parison between 2011 and 2021 - Jin-bo LI; Lan LIU; Yi MO (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo compare the prevalence and clustering of modifiable risk factors of cardiovascular disease (CVD) among rural residents of Luoping county, Yunnan province between 2011 and 2021, and to provide evidence for the prevention and treatment of CVD in the population. MethodsWith stratified multistage random sampling, two waves of survey, including face-to-face questionnaire interview and physical examination, were conducted in November 2011 and November 2021 among 3 198 and 2 580 permanent rural residents aged 35 years and over in Luoping county, Yunnan province. ResultsComplete information were collected from 3 092 and 2 539 of the residents. Compared to those in 2011, significantly decreased prevalence rates in 2021 were reported by the participants for current smoking (28.0% vs. 38.3%) , passive smoking (15.8% vs. 29.7%) , alcohol drinking (17.8% vs. 28.0%), not getting three meals a day on time (18.5% vs. 41.7%), having pickled products ≥ 3 days a week (28.9% vs. 62.8%), and consuming oily or fatty food ≥ 3 days a week (17.8% vs. 61.9%) (all P < 0.05); but significantly increased rates were detected or reported in 2021 for overweight (35.2% vs. 19.6%), obesity (13.6% vs. 4.9%), central obesity (68.0% vs. 43.7%), preference for high-salt diet (18.6% vs. 14.7%), and consuming fruits and vegetables < 3 days a week (3.2% vs. 0), respectively (all P < 0.05). The clustering rate of modifiable risk factors of CVD dropped from 90.4% in 2011 to 76.7% in 2021 among all the participants (χ2 = 195.073, P < 0.001) and the rate declined among the participants of various subgroups (all P < 0.05). Conclusion Among rural adult residents in Luoping county of Yunnan province, the prevalence rates of several modifiable risk factors of CVD decreased; while some of the rates increased in 2021 contrasting to those in 2011; but the clustering of the CVD risk factors decreased.